2021
DOI: 10.1140/epja/s10050-021-00469-w
|View full text |Cite
|
Sign up to set email alerts
|

On nuclear coalescence in small interacting systems

Abstract: The formation of light nuclei can be described as the coalescence of clusters of nucleons into nuclei. In the case of small interacting systems, such as dark matter and $$e^+e^-$$ e + e - annihilations or pp collisions, the coalescence condition is often imposed only in momentum space an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…This model was later refined and applied to cosmic ray studies and recent LHC data in Refs. [3,4] (see also Ref. [13]).…”
Section: The Wifunc Modelmentioning
confidence: 98%
See 3 more Smart Citations
“…This model was later refined and applied to cosmic ray studies and recent LHC data in Refs. [3,4] (see also Ref. [13]).…”
Section: The Wifunc Modelmentioning
confidence: 98%
“…This has motivated the suggestion that the production of light nuclei even in small interacting systems can be described using thermal models [1,[19][20][21]. One should thus mention that many of these-including the behaviour of the coalescence factor B 2 as a function of multiplicity [21] and transverse momentum in pp collisions and the decrease in the baryon emission volume with transverse momentum [22]-are naturally described by the WiFunC model [4]. In any case, current evidences for the production of a quark gluon plasma and collective motion in pp collisions are irrelevant for cosmic ray antinuclei studies since they are only observed at LHC energies.…”
Section: Alternative Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…where the deuteron wavefunction ϕ d is assumed to be a Gaussian with d = 3.2 fm [43]. The function W is the probability to find a pair of nucleons at positions r d ±r/2 with momenta p d /2 ± q.…”
Section: Deuteron Production With Coalescencementioning
confidence: 99%